2020
DOI: 10.1515/icom-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Reality based Collaboration for Design Processes

Abstract: Due to constantly and rapidly growing digitization, requirements for international cooperation are changing. Tools for collaborative work such as video telephony are already an integral part of today’s communication across companies. However, these tools are not sufficient to represent the full physical presence of an employee or a product as well as its components in another location, since the representation of information in a two-dimensional way and the resulting limited communication loses concrete object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…erefore, the technique suffers from a lack of ability to distill stylistic features. Cognitive psychology research has found that people have the observation and cognitive characteristics of recognizing objects before details, and their imagery cognition of modeling also shows the overall priority law [7]. e curve control method focuses on the local position information, so it cannot extract the overall modeling information associated with the imagery.…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…erefore, the technique suffers from a lack of ability to distill stylistic features. Cognitive psychology research has found that people have the observation and cognitive characteristics of recognizing objects before details, and their imagery cognition of modeling also shows the overall priority law [7]. e curve control method focuses on the local position information, so it cannot extract the overall modeling information associated with the imagery.…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…According to the computer-supported cooperative work time-space matrix, most existing collaboration types in IVR environments are categorized as asynchronous colocated, synchronous distributed, and asynchronous distributed collaboration; there has been relatively less research conducted on synchronous co-located collaboration [13]. In the first three collaboration types, individuals typically use different devices and engage with the virtual content at different times [11,51].…”
Section: Collaboration In Ivrmentioning
confidence: 99%
“…The implementation of collaboration in IVR is hampered by several challenges, such as geographical distance, temporal distance, and perceived distance [12]. Collaborative work can be classified according to the modalities of the space and time taxonomy as follows: synchronous co-located, asynchronous co-located, synchronous distributed, and asynchronous distributed collaboration [13,14]. Both verbal and nonverbal interactions, which are pivotal for effective group work, are diminished by the asynchrony of time and space during collaboration [15].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of collaboration in IVR is hampered by several challenges such as geographical distance, temporal distance, and perceived distance [12]. Collaborative work can be classified according to the modalities of the space and time taxonomy as follows: synchronous colocated, asynchronous co-located, synchronous distributed, and asynchronous distributed collaboration [13,14]. Both verbal and nonverbal interactions, which are pivotal for effective group work, are diminished by the asynchrony of time and space during collaboration [15].…”
Section: Introductionmentioning
confidence: 99%